Pedagogical and Psychological Characteristics of the Development Of Dysarthric Children with Severe Speech Impairments - Dzhasirkulovna, Achilova Sevara (Universitas Islam Bunga Bangsa Cirebon, 2025)
This study examines the pedagogical and psychological developmental characteristics of children with dysarthria and severe speech impairments. Through systematic observation and clinical analysis of 85 children aged 4-12 years with various speech disorders (dysarthria, rhinolalia, stuttering, alalia, and phonetic-phonemic impairments), this research investigated changes in mental processes including memory, attention, thinking, perception, and their implications for educational outcomes. The findings suggest that severe speech impairments significantly influence cognitive development and social interaction, with 73% of participants showing delayed development in at least two mental processes. Results indicated that integrated intervention involving speech therapists, psychologists, and neurologists produced measurable improvements in both speech production and cognitive function. This study highlights the critical need for early, comprehensive intervention and provides evidence for a multidisciplinary approach to treating children with severe speech impairments